2019
DOI: 10.1111/trf.15389
|View full text |Cite
|
Sign up to set email alerts
|

Updated definitions for respiratory complications of blood transfusion

Abstract: number of states and federal districts. Today's cultural landscape therefore provides a timely opportunity for the blood bank community to discuss donor and recipient safety measures in a manner that respects gender identity and that promotes inclusivity for all donors. Indeed, many of the strategies discussed above could be applied to a "genderless" DHQ. While our current understanding of donor and recipient safety is based on the binary perspective using biologic sex, considering risk factors independent of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 1 publication
0
9
1
Order By: Relevance
“…Important criteria for TACO are either respiratory compromise or pulmonary oedema [1]. In the present study, we did not find significant differences between groups in any of the markers for acute lung injury, that we measured.…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…Important criteria for TACO are either respiratory compromise or pulmonary oedema [1]. In the present study, we did not find significant differences between groups in any of the markers for acute lung injury, that we measured.…”
Section: Discussioncontrasting
confidence: 63%
“…Transfusion-associated circulatory overload (TACO) is a pulmonary transfusion complication [1]. TACO is still responsible for about one third of transfusion-related deaths in spite of adopted transfusion practices [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…This holds true for both the absolute NT‐proBNP value and the post to pre‐transfusion NT‐proBNP ratio. Since the NT‐proBNP levels were already elevated pre‐transfusion and did not significantly increase during transfusion, the NT‐proBNP ratio remained below the cutoff value of 1.5 that has been stated in the most recent definition of TACO 6 . When we explored other possible markers, we found that syndecan‐1 was elevated in TACO patients compared to non‐TACO patients at all timepoints.…”
Section: Discussionmentioning
confidence: 65%
“…Patients that had at least three criteria present were categorized as TACO. The chosen criteria were derived from the most recent TACO surveillance definition 6 . Patient data along with blood samples were available retrieved pre‐transfusion (1–2 h prior) and 1 and 24 h after transfusion.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation